Níveis tecnológicos dos agroecossistemas do milho no estado de Sergipe - Santos, Cátia dos (2012)
The changes occurred in the agriculture with the introduction of technology lead the natural resources to become more fragile when we consider the way of production developed under the conventional system, in which it keeps using machines, tractors, chemical defenses and external inputs. Through the last five years the corn agroecosystems in the State of Sergipe developed a modern agriculture, where besides being cultivated as a subsistence agriculture it has become an agribusiness, a source of income mainly in Carira and Simão Dias, the most important corn producers cities of the State. Facing the changes of the technological standards on the corn production in Sergipe, a research was made focusing on the technological level in the corn agroecosystems in the state of Sergipe. The main point was based on the analysis of the technological levels in the exploration of the corn agroecosystems in the State of Sergipe facing the changes caused by the insertion of technologies in the agriculture. A field research was made, and 15 indicators were selected and the potential and boundary points were observed. Questionnaires were applied for the data capture, besides a test of the mechanical resistance to the penetration to analyze the soil compaction. The research considered the systemic approach focusing on the environment, social and economical dimensions in the corn production in the middle- west region of Sergipe. The monoculture practice was highlighted; the excessive use of chemical defensives as well the adoption of more than 90% of the transgenic seeds among the producers. The weather become the biggest challenge for the producers in the period that the research was made for they faced an atypical condition occurred in the 2010 crop that lead not only a reduction of the production but also all the crop lost in some properties. For the soil factor, it should have used more conservative practices focusing on keeping a way of production more sustainable, in those practices the highlighted are the direct planting and the crop rotation. Generally, it should rethink the corn culture expansion mainly in Carira and Simão Dias in a way that would search to develop practices that lead in consideration not only the economical factor but also the environmental and the social ones.